2014
DOI: 10.1037/a0031142
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for fatherhood: Examining internalized heterosexism and gender-role conflict with childless gay and bisexual men.

Abstract: Research with gay and bisexual men indicates that both intemalized heterosexism and gender-role conflict have been shown to impact behaviors, roles, attitudes, and beliefs that contribute to well-being (Allen & Oleson, 1999;O'Neil, 2008; Shidio, 1994) and to decisions to become fathers (Ervin, 2004;O'Neil, 2008). With a sample of 164 gay and bisexual childless men, the present study is the first known to quantitatively examine gender-role conflict and intemalized heterosexism in relation to motivations for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Related to parenting competence and sexual orientation, some earlier research comparing lesbian and heterosexual (nonadoptive) mothers has similarly demonstrated relatively high levels of parenting competence with no differences based on mothers' sexual identities (Bos et al, 2004b). Despite previous work indicating that gay men may hold lower levels of perceived parenting efficacy because of contextual factors such as homonegative microaggressions and the stigma related to fatherhood broadly (Armesto, 2002;Robinson and Brewster, 2014), the gay fathers in our sample did not report significantly lower levels of perceived parenting competence than any other group. These results are also somewhat aligned with Goldberg and Smith's (2009) findings regarding parenting competence among LG and heterosexual parents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Related to parenting competence and sexual orientation, some earlier research comparing lesbian and heterosexual (nonadoptive) mothers has similarly demonstrated relatively high levels of parenting competence with no differences based on mothers' sexual identities (Bos et al, 2004b). Despite previous work indicating that gay men may hold lower levels of perceived parenting efficacy because of contextual factors such as homonegative microaggressions and the stigma related to fatherhood broadly (Armesto, 2002;Robinson and Brewster, 2014), the gay fathers in our sample did not report significantly lower levels of perceived parenting competence than any other group. These results are also somewhat aligned with Goldberg and Smith's (2009) findings regarding parenting competence among LG and heterosexual parents.…”
Section: Discussionmentioning
confidence: 97%
“…Stigma felt by parents about their family composition may in turn negatively affect their mental health as well as perceived competence in parenting through internalized homophobia (Herek and Garnets, 2007;Herek, 2009;Newcomb and Mustanski, 2010;Robinson and Brewster, 2014). Research has also demonstrated that internalized stigma and stress may affect relationship quality among same-gender couples (Otis et al, 2006;Frost and Meyer, 2009), so it is possible that stigma could also be relevant to other family relationships, such as between parents and children in LG adoptive parent families.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, US research on queer Experiences of childfree lesbians 3 reproductive decision making clearly evidences that queers do make reproductive choices, even those remaining childless (e.g. Mezey, 2012;Riskind & Patterson, 2010;Robinson & Brewster, 2014). Therefore, it cannot be assumed that queers are childless by default or that their childlessness is not meaningful -that it has consequences for their everyday lives and identities.…”
Section: Experiences Of Childfree Lesbiansmentioning
confidence: 99%
“…For example, during the 1970s, women in same-sex relationships often lost custody of their children from previous different-sex relationships (Clarke, Ellis, Peel, & Riggs, 2010). Furthermore, since the 1980s, there have been dramatic increases in the number of lesbian and gay people fostering, adopting, and conceiving children, a social phenomenon that has been termed the "gay baby" or "gayby" boom (Dunne, 2000;Robinson & Brewster, 2014). The focus has therefore largely been on exploring the experiences of same-sex parents and the wellbeing of children raised by them (see Robinson & Brewster, 2014), rather than on childfreedom.…”
Section: Childfreedom Within Changing Cultural Contextsmentioning
confidence: 99%